The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s11912-015-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in Prostate Cancer

Abstract: For approximately a decade, chemotherapy has been shown to prolong life in patients with metastatic castration-resistant prostate cancer (mCRPC). Since that time, however, only two agents have proven to prolong life (docetaxel and cabazitaxel). However, in the last year, the addition of chemotherapy to primary hormonal therapy became a standard of care for high-volume castration-sensitive metastatic disease. Here I will review current prostate cancer chemotherapies, mechanisms of resistance to those therapies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 72 publications
0
22
0
2
Order By: Relevance
“…Although the clinical outcome has improved, most patients with advanced PCa treated with HT eventually relapse and they develop castration-resistant PCa (CRPC) [11,12]. CRPC could be treated with sipuleucel-T, docetaxel, cabazitaxel, or abiraterone acetate plus prednisone, which was shown to prolong the survival in patients; however, CRPC is generally incurable [10][11][12][13][14]. There is therefore an urgent need for novel therapeutic strategies for CRPC.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical outcome has improved, most patients with advanced PCa treated with HT eventually relapse and they develop castration-resistant PCa (CRPC) [11,12]. CRPC could be treated with sipuleucel-T, docetaxel, cabazitaxel, or abiraterone acetate plus prednisone, which was shown to prolong the survival in patients; however, CRPC is generally incurable [10][11][12][13][14]. There is therefore an urgent need for novel therapeutic strategies for CRPC.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2), an advanced form of prostate cancer that develops when the disease progresses after initial treatment with surgery and/or medical castration using androgen deprivation therapy (ADT). Docetaxel and cabazitaxel are 2 taxane chemotherapies that are approved for treatment of metastatic CRPC (3). Recent studies have reported benefits when docetaxel was combined with ADT during the hormone-sensitive stage of the disease (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…androgen deprivation therapy reduces tumor progression, relapse frequently occurs following surgical or chemical castration. Over a decade, docetaxel is the first-line systemic chemotherapy used for metastatic castration-resistant prostate cancer (mCRPC) (2).…”
Section: Introductionmentioning
confidence: 99%